Concise illustrated dental dictionary - Harty, F. J (Wright, 1994)
The \'Concise Illustrated Dental Dictionary\' offers immediate access to the complete range of dental terminology, from basic and commonly used terms and expressions to definitions of rarely encountered conditions.
Keywords: angličtina; terminologie jako téma; Terminology as Topic; lingvistika; Dentistry; Linguistics; zubní lékařství